The effects of increased donor support time from organ donation referral to donor procurement on heart transplant recipient survival. Issue 6 (22nd February 2021) - Carter, Kristen T.; Lirette, Seth T.; Baran, David A.; Creswell, Lawrence; Kutcher, Matthew E.; Copeland, Jack G.; Copeland, Hannah
Abstract: Introduction: Given the known deleterious cardiac effects of brain death (BD) physiology, we hypothesized that time from cardiac donation referral to procurement (donor support time [DST]), would negatively impact cardiac transplant recipient survival. Methods: The United Network for Organ Sharing database was queried from 2007 to 2018, identifying 22, 593 donor hearts for analysis. Multivariate logistic models for 30‐day and 1‐year survival, as well as Cox models for overall survival and posttransplant rejection, were used to assess adjusted outcomes. Results: median DST was 3 days (interquartile range: 2–5 days). Ischemic time; distance between donor and recipient hospitals; and recipient age, creatinine, waitlist time, and length of stay were adjusted predictors of survival and rejection. DST was not associated with either outcome in aggregate; however, differential association by donor race was identified, with DST in any race recipient associated with 4% higher odds of 1‐year mortality ( p = .001; p value for interaction .005) but only a trend towards worse overall mortality ( p = .064; p value for interaction .046). Conclusion: Thus, duration of exposure to BD physiology may have a differential impact on recipient outcomes based on donor race, suggesting that additional research is needed on donor immunologic, socioeconomic, and healthcare access factors that may impact cardiac transplant recipient outcomes.